Evaluation of The Implementation of Sharia-Based Pharmaceutical Service Standards (A Qualitative Case Study) - Elmiawati Latifah; Prasojo Pribadi; Heni Lutfiyati; Cut Dewi Bunga (GHMJ (Global Health Management Journal), 2025)
Background: National health laws and best practices from other countries have helped Indonesia set standards for pharmaceutical services. However, there is still limited research on the application of Sharia principles in pharmacy services, particularly within community pharmacies. These standards are based on ideas from the Quran, Hadith, and fatwas from well-known Islamic scholars. They put these ideas into action by making sure that medicines don't contain any illegal substances, being sensitive to gender issues, and providing services that respect patients' dignity, as Islamic teachings say they should. Aims: This study aims to evaluate the implementation of Sharia-based pharmaceutical service standards through a qualitative case study at the Muhammadiyah Charity Education Pharmacy. This pharmacy's unique role as an integrated platform for pharmacy education, community service, and the application of Islamic values makes it an appropriate context for examining the implementation of Sharia-compliant pharmaceutical services. Methods: A qualitative case study design was used, involving observations and semi-structured interviews. NVivo 12 software was employed for thematic and cluster analysis. Data were coded inductively by independent researchers and validated through consensus. Pearson correlation coefficients were used to identify the strongest relationships between service quality items. The informants involved were 1 pharmacist and 3 pharmaceuticals technical staff. Results: Reliability, responsiveness, empathy, tangibles, and assurance are the themes that emerged from this study. The studies found that in the reliability dimension, fulfilling order service and distributor reliability showed the highest correlation (r=0.98), emphasizing the importance of commitment and trust in sharia-based service. In the responsiveness dimension, the most significant relationship (r=1.00) emerged between complaint resolution and clear division of duties, reflecting the role of communication and accountability. For assurance, the highest correlation (r=0.96) indicated the critical role of clear, understandable information in building trust. The empathy dimension revealed that prioritizing humanity and non-discriminatory service (r=0.52) aligned closely with the values of justice and compassion. Lastly, in the tangibles (physical) dimension, the presence of a patient prayer space showed a strong link to perceptions of cleanliness and professionalism (r=0.67), although implementation was still limited. Conclusion: By combining Islamic ethical principles with service quality metrics, the application of sharia-based service standards in pharmaceutical care improves patient satisfaction. However, some aspects still need improvement, especially the physical facilities and assurance under heavy workload. These findings provide insightful guidance on how to develop appropriate interventions, such as training programs, SOPs, and infrastructure modifications, to ensure pharmaceutical services comply with Sharia law while improving overall service quality for lawmakers, educational institutions, and businesses providing Islamic-based pharmaceutical services.